Studying pension systems and retirement age: a simple system dynamics model for a complex issue. (2016) - Tsaples, Georgios; Armenia, Stefano
One of the most challenging issues that policy makers will face in the near future is population ageing and its consequences in pension systems. The purpose of the paper is to investigate the effect of the increase in the retirement age on the pension scheme of Greece, by also taking into account social unrest that can inhibit the policy implementation. A model of Greece's pension scheme was modelled, using the methodology of system dynamics. The results showed that the increase in retirement age is not as effective as regarded in real world and under appropriate conditions, the pension scheme could be sustainable without raising the retirement age.